De-Territorialization and Re-Territorialization of"the social". A debate. - John Clarke; Fabian Kessl (Social Work and Society)
Deterritorialization has been used as an anthropological concept to designate the weakened ties between culture and place: Certain cultural/social processes and relations seem to increasingly transcend their previously given territorial boundaries in flexible capitalist societies. At the same time, policy studies, especially Studies on Governmentality, have emphasized the re-territorialization of the social, in which the former national welfare arrangements (welfare and nation state) as the scale of bio-political integration patterns are more and more substituted by small scaled inclusion areas (e.g. neighbourhoods, districts and communities). Drawing on Deleuze and Guattari, de-territorialization processes have therefore always to be understood as combined with processes of a re-territorialization, producing new spatial formations. In this view, spatial arrangements and connections are not given and static structures, but controversial and unstable - nevertheless they are influential.